2000
DOI: 10.1007/bf02664762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary α‐linolenic acid on the conversion and oxidation of13C‐α‐linolenic acid

Abstract: The effects of a diet rich in alpha-linolenic acid vs. one rich in oleic acid on the oxidation of uniformly labeled 13C-alpha-linolenic acid and its conversion into longer-chain polyunsaturates (LCP) were investigated in vivo in healthy human subjects. Volunteers received a diet rich in oleic acid (n = 5) or a diet rich in alpha-linolenic acid (n = 7; 8.3 g/d) for 6 wk before and during the study. After 6 wk, subjects were given 45 mg of 13C-alpha-linolenic acid dissolved in olive oil. Blood samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
86
3
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 24 publications
15
86
3
2
Order By: Relevance
“…However, amounts of 13 C18X2n-6 and its 13 C labelled LCPs varied considerably between the subjects. In a recent similar study with 13 C a-linolenic acid (Vermunt et al, 2000), we found a signi®cant negative correlation between plasma 13 C LCPs and the 13 C elimination with breath CO 2 . In the present study, in the three subjects of whom 13 C elimination was known, the subject with the highest amounts of 13 C LCPs had also the lowest 13 C elimination by breath and vise versa.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, amounts of 13 C18X2n-6 and its 13 C labelled LCPs varied considerably between the subjects. In a recent similar study with 13 C a-linolenic acid (Vermunt et al, 2000), we found a signi®cant negative correlation between plasma 13 C LCPs and the 13 C elimination with breath CO 2 . In the present study, in the three subjects of whom 13 C elimination was known, the subject with the highest amounts of 13 C LCPs had also the lowest 13 C elimination by breath and vise versa.…”
Section: Discussionsupporting
confidence: 70%
“…Thereafter, lipid extracts were hydrolyzed and the resulting fatty acid methylated (Lepage & Roy, 1986). The absolute fatty acid composition in plasma total lipids was analyzed using a gas chromatograph with a¯ame ionization detector (GCaFID, Perkin Elmer, Norwalk, Connecticut, USA) as described before (Vermunt et al, 2000).…”
Section: Blood Sampling and Analysismentioning
confidence: 99%
“…No differences were observed on EPA and DHA levels in any of the piglet tissues between 2% and 1% maternal linseed oil feeding, indicating that the additional ALA was not further converted to its LC derivatives, but partially metabolized to 20:3n-3 and partially stored as ALA in the muscle tissue. Oxidation was not measured in this study, but it has already been suggested that diets high in ALA also increase the oxidation of ALA, thereby reducing its conversion to EPA (Vermunt et al, 2000).…”
mentioning
confidence: 77%
“…Eicosapentaenoic (EPA; C20:5n-3) and docosahexaenoic acid (DHA; C22:6n-3) are n-3 HUFA and are primarily found in fatty fish. Although there is a biosynthetic pathway from the precursor -linolenic acid (C18:3n-3) into EPA and DHA (Emken et al 1994, Cho et al 1999, Salem et al 1999, Vermunt et al 2000, Pawlosky et al 2001, the quantitative contribution of this pathway to tissue EPA and DHA levels is unclear. In contrast to EPA and DHA, -linolenic acid is found in vegetables, walnuts and vegetable oils (e.g.…”
Section: Introductionmentioning
confidence: 99%